Perempuan, Islam, dan Wacana Kolonial: Pembacaan Pascakolonial terhadap Novel Ratu yang Bersujud (2013) Karya Mahdavi - Dwi Susanto; Rianna Wati; Afnan Arummi (Universitas Mulawarman, 2021)
Representations of women, Islam, and colonial discourses appear in the Ratu yang Bersujud (2013). The novel is a counter discourse towards the representation of women and Islam in global discourse. The main problem of this research is the representation of Islam and women towards the Western world within the perspective of the author's subject. The purpose is to show the representation of Islam and women according to the author's subject view. This research uses a post-colonial perspective, especially the way colonized subjects present re-representation or overwriting. The objects are the Ratu yang Bersujud (2013) and the views of colonized subjects on the representation of Islamic identity (women and Islam). This research data consists of text narrative structure, thematic ideas of the text, social context of the author or colonized society, and discourse of modern colonialism. The result of the research is that the author's subject carries out a deconstruction that leads to the defense or resistance to the image or representation of Islam and women in the global discourse. However, it is trapped in ambiguity, which is trapped in colonial discourse and does not voice women in Islam but Islamic identity in the perspective of the patriarchal subject. It is proven as a representation of women as objects of misfortune.